2022
DOI: 10.3847/1538-4357/ac752a
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in Early Optical Afterglows of Gamma-Ray Bursts Driven by Precessing Jets

Abstract: Jet precessions are widely involved in astrophysical phenomena from galaxies to X-ray binaries and gamma-ray bursts (GRBs). Polarization presents a unique probe of the magnetic fields in GRB jets. The precession of GRB relativistic jets will change the geometry within the observable emitting region of the jet, which can potentially affect the polarization of the afterglow. In this paper, we take into account jet precession to study the polarization evolution and corresponding light curves in GRB early optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In this case, the X-ray afterglows are likely to contain several X-ray flares of similar widths in linear scale and similar spectra, and the optical afterglow light curve will show sharp rebrightening signatures (Chen et al 2022). While in the jet precession scenario, it is expected that peculiar polarization features in early optical afterglows (Huang & Liu 2022) and special energy injection signatures in X-ray/optical afterglows (Huang & Liu 2021) will be observed . Lin et al (2022) performed a systemic search among ∼3000 GRBs, and only four GRBs are found to consist of multiple similar emission episodes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the X-ray afterglows are likely to contain several X-ray flares of similar widths in linear scale and similar spectra, and the optical afterglow light curve will show sharp rebrightening signatures (Chen et al 2022). While in the jet precession scenario, it is expected that peculiar polarization features in early optical afterglows (Huang & Liu 2022) and special energy injection signatures in X-ray/optical afterglows (Huang & Liu 2021) will be observed . Lin et al (2022) performed a systemic search among ∼3000 GRBs, and only four GRBs are found to consist of multiple similar emission episodes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our results suggest to us to be careful when identifying millilensing GRBs. Multiband afterglow data and especially angular offset detections are essential to provide comprehensive justification of such an identification (Huang & Liu 2021;Chen et al 2022;Huang & Liu 2022).…”
Section: Introductionmentioning
confidence: 99%